The Long-Term Change of Arrhythmias after Transcatheter Closure of Perimembranous Ventricular Septal Defects - Hongyan Zheng; Aiwen Lin; Li Wang; Yukai Xu; Zhiwei Zhang (Cardiology Research and Practice)
Objectives. To observe and analyze the long-term change of different types of arrhythmias after transcatheter closure of perimembranous ventricular septal defect (pmVSD). Methods. We retrospectively collected the data of patients who underwent pmVSD closure in our institution from March 2002 to December 2010. Results. One hundred thirty-nine patients met the inclusion criteria, of which 265 (25.5%) had early arrhythmia. They were classified into two categories: conduction abnormality (191/1039; 18.4%) and origin abnormality (94/1039; 9.0%), including 20 patients with both types of arrhythmias. The median follow-up time was 84.5 months, and 103 patients (103/191; 53.9%) with early conduction block got permanent arrhythmias, while only three patients (3/94; 3.2%) with early anomalous origin arrhythmias still had an abnormal electrocardiogram. Serious arrhythmias (28/1039; 2.7%), including II° atrioventricular block (AVB), III° AVB, and complete left bundle branch block (CLBBB), can appear immediately in the early postoperative period (21 patients) or in the late outset (seven patients) after several months or even years (6 months to 8.3 years). Twenty patients (20/21; 95.2%) with serious arrhythmia in the early postoperative period improved after early treatment, but six patients relapsed or worsened during follow-up. At the endpoint, severe arrhythmia persisted in 13 patients, of which four patients got permanent pacemaker implanted, and one patient with recurrent CLBBB died from heart failure. Conclusions. The probability of delayed CAVB or bundle branch block after VSD closure is low but often occurs several years after surgery. Therefore, long-term ECG follow-up should last for several years or even decades. Serious arrhythmias that appear early after transcatheter pmVSD closure may impose a risk of recurrence although they have been cured already. Close attention should be paid to the changes of cardiac function in patients with CLBBB after VSD closure, and the severity of such arrhythmia should be taken seriously and reexamined.